Recognition of a translocation motif in the regulator HpaA from Xanthomonas euvesicatoria is controlled by the type III secretion chaperone HpaB - Drehkopf, Sabine; Otten, Christian; Büttner, Daniela (Frontiers in Plant Science, 2022)
The Gram-negative plant-pathogenic bacterium Xanthomonas euvesicatoria is the causal agent of bacterial spot disease in pepper and tomato plants. Pathogenicity of X. euvesicatoria depends on a type III secretion (T3S) system which translocates effector proteins into plant cells and is associated with an extracellular pilus and a translocon in the plant plasma membrane. Effector protein translocation is activated by the cytoplasmic T3S chaperone HpaB which presumably targets effectors to the T3S system. We previously reported that HpaB is controlled by the translocated regulator HpaA which binds to and inactivates HpaB during the assembly of the T3S system. In the present study, we show that translocation of HpaA depends on the T3S substrate specificity switch protein HpaC and likely occurs after pilus and translocon assembly. Translocation of HpaA requires the presence of a translocation motif (TrM) in the N-terminal region. The TrM consists of an arginine- and proline-rich amino acid sequence and is also essential for the in vivo function of HpaA. Mutation of the TrM allowed the translocation of HpaA in hpaB mutant strains but not in the wild-type strain, suggesting that the recognition of the TrM depends on HpaB. Strikingly, the contribution of HpaB to the TrM-dependent translocation of HpaA was independent of the presence of the C-terminal HpaB-binding site in HpaA. We propose that HpaB generates a recognition site for the TrM at the T3S system and thus restricts the access to the secretion channel to effector proteins. Possible docking sites for HpaA at the T3S system were identified by in vivo and in vitro interaction studies and include the ATPase HrcN and components of the predicted cytoplasmic sorting platform of the T3S system. Notably, the TrM interfered with the efficient interaction of HpaA with several T3S system components, suggesting that it prevents premature binding of HpaA. Taken together, our data highlight a yet unknown contribution of the TrM and HpaB to substrate recognition and suggest that the TrM increases the binding specificity between HpaA and T3S system components.